Cu2O photocathodes with band-tail states assisted hole transport for standalone solar water splitting - Linfeng Pan (Nature Portfolio, 2020)
While solar-to-fuel conversion offers a promising technology to produce energy, device components can limit light absorption and reduce performances. Here, authors show copper thiocyanate to assist hole transport in photoelectrodes and enable a 4.55% solar-to-hydrogen efficiency in tandem devices.